“DEVELOPING STRENGTH AND ENDURANCE IN VISUALLY IMPAIRED STUDENTS THROUGH ADAPTIVE AND INTERACTIVE TRAINING” - Qurbonova Nasiba Mirsalim qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines strategies for improving strength and endurance in visually impaired students using adaptive and interactive training methods. The study focuses on preparatory classes where exercises are tailored to individual needs and include tactile, auditory, and guided activities. The research highlights the importance of individualized instruction, safety, and motivation in enhancing physical development.